Tradisi Sebagai Representasi Wong Tengger atas Perubahan Sosial Persepektif Cultural Studies - Rizqi Amaliani (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
This article explores the dynamics of Wong Tengger to maintain the culture of the supremacy of the Indonesian government and the expansion of Islam. This study took the locus in several villages in the Mount Bromo area such as Ngadas, Ngadisari, and Wonokerto, Probolinggo Regency. By using cultural studies theory and representation theory perspective, this journal collaborates with Wong tengger's strategy to represent identity in the midst of social change. The dialectical dynamics that occurred between Tengger and the supremacy resulted in two hypotheses. First, due to the strong tradition and culture of Wong Tengger both with Hindu and Islamic ideologies, it is interpreted as a cultural system that is only attached symbolically. Second, although it is considered syncretic, Islam or Hinduism actually creates Wong Tengger's word view substantially and culturally. This second view, if considered, is similar to the religious system of the people in Java in general who adhere to the